1977
DOI: 10.1093/bja/49.9.927
|View full text |Cite
|
Sign up to set email alerts
|

Some Circulatory and Respiratory Effects of Morphine in Patients Without Pre-Existing Cardiac Disease

Abstract: SUMMARYHaemodynamic and respiratory effects of i.v. morphine (10 mg/70 kg body weight) were studied in 10 adults with unimpaired circulatory function. There were significant changes in mean arterial pressure, mean heart rate, respiratory rate and tidal volume, at 10-, 30-and 60-min intervals. Transient changes in mean total systemic resistance and mean stroke volume were also seen at 10 min. The results strongly suggest a peripheral vasodilator response to morphine. Respiratory depression was not demonstrated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Morphine is known to have different side effects, the one most recognized being the dose-dependent respiratory depression, whereas it is usually associated with relatively limited cardiovascular effects. 14 In NHPs, a long-lasting reduction in MV was observed reaching statistical significance at one time-point, that is, 5.50 hours following treatment. Morphine also decreased BP in NHPs, reaching statistical significance at 4.25 and 14.50 hours post-injection.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Morphine is known to have different side effects, the one most recognized being the dose-dependent respiratory depression, whereas it is usually associated with relatively limited cardiovascular effects. 14 In NHPs, a long-lasting reduction in MV was observed reaching statistical significance at one time-point, that is, 5.50 hours following treatment. Morphine also decreased BP in NHPs, reaching statistical significance at 4.25 and 14.50 hours post-injection.…”
Section: Discussionmentioning
confidence: 88%
“…Morphine also decreased BP in NHPs, reaching statistical significance at 4.25 and 14.50 hours post-injection. 14,15 In Beagle dogs, morphine had no statistically significant effect on respiratory and cardiovascular parameters, although a trend toward lower RR values was observed. This observation is somewhat unexpected as morphine administration in dogs has been shown to induce respiratory depression in this species.…”
Section: Discussionmentioning
confidence: 95%
“…2 ). There was no statistically significant association between medication administration and change in tidal volume for opioids (11% decrease, 95% CI 28% decrease-5% increase, 6 arms) 39 , 55 , 56 and other hypnotic agents (9% decrease, 95% CI 23% decrease-6% increase, 6 arms) 23 , 36 , 41 , 44 , 49 ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 96%
“…A total of 44 studies with 56 arms reported respiratory rate in patients breathing without mechanical ventilation. Opioids were associated with a statistically significant mean reduction in respiratory rate of 18% (95% CI 12–24%, p < 0.0001, 24 arms), 15 , 20 , 21 , 33 , 35 , 39 , 46 , 51 , 55 , 56 , 61 , 62 , 65 whereas inhaled sevoflurane was associated with an increase in respiratory rate of 83% (95% CI 49–118%, p < 0.0001, 1 arm). 28 Mean percent changes in respiratory rate were close to zero and not statistically significant with exposure to benzodiazepines (2% decrease, 95% CI 9% decrease-6% increase, 16 arms), 19 , 26 , 27 , 29 , 37 , 42 , 43 , 47 , 50 , 59 , 63 , 64 other hypnotic agents (2% decrease, 95% CI 9% decrease-5% increase, 17 arms), 17 , 23 , 26 , 29 , 30 , 31 , 32 , 34 , 36 , 41 , 44 , 48 , 49 , 59 and propofol (4% increase, 6% decrease-14% increase, 9 arms) 16 , 17 , 30 , 41 , 52 , 54 , 60 , 61 , 63 ( Fig.…”
Section: Resultsmentioning
confidence: 98%